2005
DOI: 10.1021/ol050148t
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Synthesis of Decarestrictine D from a Previously Inaccessible (2Z,4E)-Alkadienyl Alcohol Precursor

Abstract: [reaction: see text] The core structure of decarestrictine D was constructed by stereoselective oxygenation of (2Z,4E)-alkadienyl alcohol, which could be synthesized by a nickel-catalyzed coupling reaction between the corresponding cis bromide and trans borate. Efficiency in macrocyclization of the seco acid with Yamaguchi reagent was found to be protective-group-dependent, and the best yield of 40% was obtained with the seco acid with tri-MOM protective groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 38 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…Interestingly, some of these cephalosporolides were also isolated recently from other natural sources such as Cordyceps militaris BCC 2816, Beauveria bassiana , and/or wood decay fungus Armillaria tabescens (strain JNB-OZ344) . Structurally, these cephalosporolides ( 1 – 6 ) are 10-membered lactones (namely decanolides) with a methyl group at C9, resembling to other bioactive decanolides . However, the structural skeleton of cephalosporolides E and F (Ces-E, 7 , and Ces-F, 8 ) characterized by the presence of 5,5-spiroketal- cis -fused-γ-lactone was unprecedented at the time of their isolation but found in other recently isolated natural products such as cephalosporolides H and I, penisporolides, and ascospiroketals …”
mentioning
confidence: 99%
“…Interestingly, some of these cephalosporolides were also isolated recently from other natural sources such as Cordyceps militaris BCC 2816, Beauveria bassiana , and/or wood decay fungus Armillaria tabescens (strain JNB-OZ344) . Structurally, these cephalosporolides ( 1 – 6 ) are 10-membered lactones (namely decanolides) with a methyl group at C9, resembling to other bioactive decanolides . However, the structural skeleton of cephalosporolides E and F (Ces-E, 7 , and Ces-F, 8 ) characterized by the presence of 5,5-spiroketal- cis -fused-γ-lactone was unprecedented at the time of their isolation but found in other recently isolated natural products such as cephalosporolides H and I, penisporolides, and ascospiroketals …”
mentioning
confidence: 99%
“…Literature search indicated that many decanolide natural products such as aspinolides, stagonolides, modiolides, and decarestricktines have actually aroused great synthetic interest for their ubiquitous natural sources, broad‐spectrum bioactivities, and the synthetic challenges for cyclization of acyclic precursors to the medium‐sized lactones due to the enthalpy and entropy constrains. The two prevailed methods for the construction of such medium‐sized macrolactones are macrolactonization and ring‐closing metathesis . Not surprisingly, these two methods were adapted to the total syntheses of the decanolide‐type cephalosporolides, which are summarized in the following sub‐section.…”
Section: Total Syntheses Of the Decanolide–type Cephalosporolides B mentioning
confidence: 99%
“…Recentemente, Kobayashi et al 30 relataram uma síntese estereosseletiva da decarestrictina D, utilizando ainda o mesmo reagente de lactonização (Esquema 6). Neste artigo, os autores discutem a influência de diferentes grupos protetores das hidroxilas na eficiência da reação, sendo que o melhor rendimento (40%) foi obtido quando se usou o grupo metóximetil éter (MOM).…”
Section: Esquema 1 Esquema 2 Esquemaunclassified